THE RESEARCH OF THE POLLUTION OF SPRINGS IN THE CITY OF STAVROPOL BY THE METHOD OF FACTOR ANALYSIS - Inna Vladimirovna Begday; Elena Vasilievna Bondar; Natalya Evgenyevna Perekopskaya (Наука. Инновации. Технологии, 2022)
The researches of pollution of six springs in Stavropol were made according to thirteen kinds of contamination by factor analysis. Analysis of samples was carried out on the basis of Scientific-Educational Laboratory «Ecoanalytical Laboratory of Environmental Research» CCU NCFU; using the following instruments: atomic absorption spectrometer with flame atomiza-tion at ICE 3300 (ThermoScientific, USA), conductivity meter «Expert-002», spectrophotometer «the Genesys' model 10s (ThermoScientific, USA), pH meter pH 150MI. Correlation matrix of monory relations (correlation of factors between each other) and binary relations (correlation between different factors) were compiled. Binary relations with correlation coefficients in the range 0,3 < r